1998
DOI: 10.1016/s0042-6989(98)00071-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial cone activity distribution in diseases of the posterior pole determined by multifocal electroretinography

Abstract: Thirty patients with a reduced central vision due to diseases of the posterior pole were examined with the VERIS system developed by Sutter and Tran (Vis Res 1992;32:433-446) to characterize the topography of electroretinographic (ERG) changes in comparison to the results in 30 normal volunteers. Diagnoses included Stargardt's macular dystrophy (SMD, n = 10), age-related macular degeneration (AMD, n = 5), cone dystrophy (CD, n = 5), central retinal vein occlusion (CRVO, n = 5), and autosomal dominant optic atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 16 publications
3
18
0
5
Order By: Relevance
“…167 The extent of mfERG changes is influenced by the severity of AMD as patients with neovascular AMD had more severe reductions in mfERG response amplitudes and delays in implicit times compared with patients with dry AMD. 110,152 Palmowski et al reported that the functional changes demonstrated by mfERG corresponded well with the anatomical changes detected on fluorescein angiography. 228 However, this was only based on the results from three AMD patients and subsequent studies have demonstrated that the mfERG abnormality tends to be more diffuse compared with the morphological changes.…”
Section: Clinical Applications Of Mferg In Acquired Retinal Diseases mentioning
confidence: 84%
See 2 more Smart Citations
“…167 The extent of mfERG changes is influenced by the severity of AMD as patients with neovascular AMD had more severe reductions in mfERG response amplitudes and delays in implicit times compared with patients with dry AMD. 110,152 Palmowski et al reported that the functional changes demonstrated by mfERG corresponded well with the anatomical changes detected on fluorescein angiography. 228 However, this was only based on the results from three AMD patients and subsequent studies have demonstrated that the mfERG abnormality tends to be more diffuse compared with the morphological changes.…”
Section: Clinical Applications Of Mferg In Acquired Retinal Diseases mentioning
confidence: 84%
“…14,54,56,57,72,91,110,122,151,152,167,172,228,248,258 Patients with early AMD were found to have significant reduction in the foveal P1 amplitude and delay in N1 implicit time compared with normal age-matched controls. 167 The extent of mfERG changes is influenced by the severity of AMD as patients with neovascular AMD had more severe reductions in mfERG response amplitudes and delays in implicit times compared with patients with dry AMD.…”
Section: Clinical Applications Of Mferg In Acquired Retinal Diseases mentioning
confidence: 97%
See 1 more Smart Citation
“…Various studies have reported the efficacy of the mfERG in the assessment of ARMD [6,19,20,29,33,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Multifocal Ergmentioning
confidence: 99%
“…16,17 This test used the Visual Evoked Response Imaging System (version 4.9, EDI Inc., CA) with dilated pupils. Both eyes were tested simultaneously.…”
Section: Introductionmentioning
confidence: 99%